The Effect of Implementation of Independent Curriculum on Learning Interest and Character of Elementary School Students - Sulfadli; Supartinah (Postgraduate, University of Mataram, 2023)
The purpose of this study is to find facts that are compatible with the implementation of the independent curriculum on learning interest and also the character of elementary school students who have carried out the learning process by implementing the independent curriculum itself, this research uses the survey method with data collection techniques using observation and also questionnaires while for The population of this study is 10 teachers and 22 grade IV students. The analysis includes validity and reliability tests, normality tests, linearity tests and hypothesis tests with the research results showing a significant influence between the implementation of the independent curriculum on students' interest in learning and character values ​​with a sig value of 0.000 where <0.05, this shows that the implementation The independent curriculum has brought many changes and influences on elementary school students, including the interests and character of students. Therefore, teachers need to use more learning processes with independent curriculum designs in each class and schools can prepare facilities and infrastructure so that they can produce optimal learning processes so that they get the expected results in accordance with the goals of the school itself and improve the quality of existing education in Indonesia.